The Freeman Book Awards - Nancy Hope (Education About Asia, 2026)
The Freeman Book Awards, which are sponsored by National Consortium for Teaching about Asia (NCTA), the Committee on Teaching about Asia (CTA) of the Association for Asian Studies (AAS), and Asia for Educators (AFE) at Columbia University, recognize quality literature for children and young adults that contribute meaningfully to an understanding of East and Southeast Asia at age-appropriate levels. Over the past ten years, more than one hundred titles have been recognized in the four categories of: (1) Children’s Literature (picture books for up to grade five); (2) Young Adult: Middle School Literature; (3) Young Adult: High School Literature; and (4) Young Adult: Middle and High School Graphic Novels.
Keywords: Books; Literature; Young Adults; Asia; East Asia; Southeast Asia; Freeman